Effect of particle size distribution on the in vitro digestion of calcium alginate‐starchy model foods. (22nd May 2019) - Ramírez, Cristian; Millón, Camila; Nuñez, Helena; del Campo, Valeria; Almonacid, Sergio; Simpson, Ricardo
Abstract: The aim of this study was to investigate through the use of Weibull and Multiscale kinetics models the effect of different particle size distributions on starch hydrolysis during in vitro digestion of calcium alginate filled with gelatinized potato starch as model foods. Three‐different model foods (calcium alginate and gelatinized starch with a without alginate beads) were used. Three particle size distributions by applying the amount of 5, 10, and 15 compression cycles were generated and characterized by Rosin‐Rammler model. The different particle distributions were in vitro digested and starch hydrolysis was quantified. The results showed significant differences ( p  > .05) between the three particle size distributions. In general, the particle size affected the starch hydrolysis, but structured model food produced a lower hydrolysis (~73%) compared to nonstructured food (>90%). These results also showed that incorporation of beads played an important role in modulating starch hydrolysis. The Weibull‐model ( R 2  > 0.95) and Multiscale kinetics‐model ( R 2  > 0.98) were fitted to starch hydrolysis curves. The parameters of both models were able to explain the hydrolysis behavior for the different kind of structures and particle size distributions studied. This study showed that particle size distribution or incorporation of small beads can determine the starch hydrolysis during in vitro digestion. Practical application: The chewing process has as main objective to reduce the food to small particles. These particles have a size distribution which will be dependent on the number of chewing cycles that are applied. This distribution can be determinant in the following step of digestion, especially at the intestinal level where carbohydrate hydrolysis mainly occurs. The results showed how food structuring can affect the particle size distributions with the consequent of modulating starch hydrolysis during in vitro digestion of gelatinized potato starch. Certainly, this study, beyond presenting a way to simulate the chewing process, showed the importance to consider a method to produce a particle size distribution which can impact on nutrient release. Finally, for food industry could be useful to have information about how the particle size affect the amount of nutrients that can be obtained from the food, mainly to be informed to consumers into the nutrition facts. Abstract :